2007
DOI: 10.3155/1047-3289.57.12.1461
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hydrogen Sulfide and Sulfur Dioxide by Carbons Impregnated with Triethylenediamine

Abstract: Activated carbon (AC) adsorption has long been considered to be a readily available technology for providing protection against exposure to acutely toxic gases. However, ACs without chemical impregnation have proven to be much less efficient than impregnated ACs in terms of gas removal. The impregnated ACs in current use are usually modified with metalloid impregnation agents (ASC-carbons; copper, chromium, or silver) to simultaneously enhance the chemical and physical properties of the ACs in removing specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…According to [102], increasing the potassium iodide content of AC-KI to 16% improves its protective properties against SO 2 (τ pa (SO 2 )) according to equation (5); then when ωKI increases to 22%, this characteristic approaches an almost horizontal asymptote, after which it sharply decreases. This indicates that at high contents, KI (like K 2 CO 3 [5], 1,8-diazobicyclooctane (DABCO) [106], triethanolammonium citrate (1:3) [107]) aggregates and/or blocks AC pores, which limits the accessibility of I 2 for SO 2 . Along with this, increasing the KI content lowers the sorption capacity of KI with respect to C 6 H 6 according to equation (6): where τ pa (SO 2 ) is the time of the protective action against SO 2 (min) at СSO 2 = 150 mg/m 3 , a relative humidity of the GAM of 90-95%, a flow rate of the GAM of 2.0 cm/s; τ pa (C 6 H 6 ) is the time of protective action against C 6 H 6 (min) at С 6 H 6 = 500 mg/m 3 , a relative humidity of the GAM of 90-95%, a flow rate of the GAM of 2.0 cm/s); ωKI is the mass fraction of KI, %.…”
Section: Phisical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…According to [102], increasing the potassium iodide content of AC-KI to 16% improves its protective properties against SO 2 (τ pa (SO 2 )) according to equation (5); then when ωKI increases to 22%, this characteristic approaches an almost horizontal asymptote, after which it sharply decreases. This indicates that at high contents, KI (like K 2 CO 3 [5], 1,8-diazobicyclooctane (DABCO) [106], triethanolammonium citrate (1:3) [107]) aggregates and/or blocks AC pores, which limits the accessibility of I 2 for SO 2 . Along with this, increasing the KI content lowers the sorption capacity of KI with respect to C 6 H 6 according to equation (6): where τ pa (SO 2 ) is the time of the protective action against SO 2 (min) at СSO 2 = 150 mg/m 3 , a relative humidity of the GAM of 90-95%, a flow rate of the GAM of 2.0 cm/s; τ pa (C 6 H 6 ) is the time of protective action against C 6 H 6 (min) at С 6 H 6 = 500 mg/m 3 , a relative humidity of the GAM of 90-95%, a flow rate of the GAM of 2.0 cm/s); ωKI is the mass fraction of KI, %.…”
Section: Phisical Chemistrymentioning
confidence: 99%
“…To remove acidic gaseous pollutants, IAC materials based on impregnating solutions of N-containing organic bases are used: monoethanolamine (MEA) [108][109][110][111], diethanolamine (DEA) [109,110,112], triethanolamine (TEA) [113], DABCO [14,106,112,[114][115][116], N-methyldiethanolamine (MDEA) [118], pipe razine [111], etc., similarly to [119,120]. IACs based on N-containing organic bases are also widely used for the sanitary removal of formaldehyde from the air [121].…”
Section: Phisical Chemistrymentioning
confidence: 99%
“…Aqueous solutions of alkanolamines are commonly used to remove H 2 S, but they cannot reduce the sulfur content to the low levels required (Xu et al, 2005). Among the methods used to remove low concentration H 2 S/SO 2 from mixture gases, adsorption by porous materials such as activated carbons (AC) (Bagreev and Bandosz, 2001;Bandosz, 1999;Guo and Lua, 2002), ammonia-treated activated carbon fibers (Mangun et al, 2001), impregnated activated carbon (Bandosz et al, 2000;Wu et al, 2007;Xiao et al, 2008), zeolites (Cosoli et al, 2008;Melo et al, 2006), metal organic frameworks (MOFs) (Hamon et al, 2009;Xiang et al, 2011), is an efficient and economical approach. For example, Cosoli et al (2008) simulated H 2 S removal from biogas by zeolites and confirmed that hydrophilic zeolites are more suitable for H 2 S adsorption.…”
Section: Introductionmentioning
confidence: 99%